THE PERSEPSI GURU BAHASA INGGRIS TERKAIT DENGAN BUKU AJAR YANG DISEDIAKAN OLEH PEMERINTAH SEBAGAI BAHAN AJAR UTAMA - Esa Penilta Amiruddin; Nining Syafitri (English Education Department, 2021)
English textbook from government is issued for all the Indonesian students in junior high school. It should be used as the primary teaching material in English class. In fact, the English teachers in SMPN 4 Baubau meet some difficulties in applying that policy. The objective of this research was to find out the perception of English teachers related to textbook provided by government as a primary teaching material. This research used descriptive qualitative method with design case study. The sample of this research was three English teachers in SMPN4 Baubau. The findings showed the teachers did not use the government’s textbook as the primary but it was employed as the supporting teaching material and the teachers used other books from non-government publishers as the main textbook.